EXTRACTION, PARTIAL PURIFICATION AND CHARACTERIZATION OF BETA-GLUCOSIDASE FROM APRICOT DEFATTED SEEDS POWDER - Hind K. A.,; K. A. Shakir, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The objective of this study, is characterization of partially purified beta-glucosidase (BGS) extracted from apricot defatted seeds powder. The enzyme was extracted using sodium phosphate solution (0.2M, pH 7) containing 2% sodium chloride with mixing ratio of (1:5 solid: liquid) for extraction period of 3 hours at 4C. The crude extract was precipitated by ammonium sulfate at 20-70% saturation, dialyzed then concentrated.  The specific activity of the enzyme, folds of purification and the enzymatic yield were 5.45 units/mg, 7.8 fold and 84.5%, respectively. The results showed that the optimum conditions for the enzyme activity were at pH 5.5 and 6.5, the optimum temperature for the enzyme’s activity was 40°C and 55°C, while the thermal stability of the enzyme was between 25-45°C when the enzyme retained more than 90% of its activity over 30 minutes incubation at the optimum pH for activity, and retained 88% of its activity at 50° C. The results also revealed the inhibitory and activator effects of minerals and chemical compounds on the BGS activity.